2010
DOI: 10.1016/j.jcrysgro.2009.09.057
|View full text |Cite
|
Sign up to set email alerts
|

Heteroepitaxial ZnO nano hexagons on p-type SiC

Abstract: Abstract

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
25
0

Year Published

2011
2011
2015
2015

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 28 publications
(25 citation statements)
references
References 34 publications
(15 reference statements)
0
25
0
Order By: Relevance
“…We believe that the fact that SiC substrate is 4° off-cuted favours the nucleation of ZnO nanocrystalls and their epitaxial growth. Earlier we reported in details the growth of ZnO HEX on SiC substrates, assisted by high quality hetero interface and advanced optical properties [24]. We suppose, that the observed features provide the necessary premise for the epitaxial growth of high quality ZnO nanostructures on SiC for unique applications.…”
Section: Zno Nanostructures Grown At Low Precursor Pressurementioning
confidence: 69%
See 1 more Smart Citation
“…We believe that the fact that SiC substrate is 4° off-cuted favours the nucleation of ZnO nanocrystalls and their epitaxial growth. Earlier we reported in details the growth of ZnO HEX on SiC substrates, assisted by high quality hetero interface and advanced optical properties [24]. We suppose, that the observed features provide the necessary premise for the epitaxial growth of high quality ZnO nanostructures on SiC for unique applications.…”
Section: Zno Nanostructures Grown At Low Precursor Pressurementioning
confidence: 69%
“…It was concluded that the plasma discharge promotes the precursors decomposition and increases the ZnO adatoms mobility, resulting in high quality film formation [23] at lowered temperatures. Recently the integration of the ZnO nanostructures with Si and SiC via APMOCVD has been reported to result in advanced structural and optical properties [24,9]. Here, we applied varying precursor pressure for growth of ZnO nanostructures.…”
Section: Precursors Chemistrymentioning
confidence: 99%
“…10,12 Zn acetylacetonates [Zn(AA) 2 ] and oxygen were used as precursors. Argon gas flow transported the vapor of the thermally decomposed Zn precursor to the reaction zone where due to mixing with oxygen, the ZnO deposits onto the substrate.…”
Section: Methodsmentioning
confidence: 99%
“…The high quality of these nocrystallites explains the intense light emission in the ultraviolet spectral region. 10 The present investigation is important due to the anomalies reported on the epitaxial growth of ZnO on 6H-SiC. 11 The ZnO nanopillars were also deposited on SiO 2 /Si wafers, and the difference in the mode of growth of these nanocrystallites in comparison to the ZnO grown on SiC is discussed.…”
mentioning
confidence: 98%
“…Earlier, we demonstrated the change of the texture of the ZnO films from (0001) to (10-11) via Ga doping and the morphology control via respective annealing (144,145). We have recently reported on the control of ZnO nanostructure location and inclination via respective substrate miss cut in the epitaxial growth of ZnO on 4H-SiC (13). Such an approach can be utilized for fabrication of the active ZnO elements for biosensors, being able for operation in liquid.…”
Section: Recent Achievements In Zno Nanocrystal Based Biosensorsmentioning
confidence: 99%